Decision-Theoretic Prediction and Policy Design of GDP Slot Auctions - Bono, James; Grana, Justin; Wolpert, David; Xie, Dongping (AIAA 2014, 2014)
We examine the potential for a simple auction to allocate arrival slots during Ground Delay Programs (GDPs) more efficiently than the currently used system. We find that the second-price slot auction has the potential to lower social costs but further analysis is needed to determine which pre-GDP schedules are best suited for an auction. The analysis of these auctions uses Predictive Game Theory (PGT) Wolpert and Bono (2013, 2010), a new approach that produces a probability distribution over strategies instead of an equilibrium set. Furthermore, the slot auction game of this paper represents the first application of PGT to a game of imperfect information and to a pure strategy space.